Using indirect comparisons in pharmacoeconomic examination - Yu. E. Balykina; A. S. Kolbin (Фармакоэкономика)
Health technology assessment is a fundamental tool while choosing the most cost- and clinical effective technologies that are being introduced into the health system. The basis for assessment is the data of clinical studies. The experts are interested in not only the effect of a new medical technology, but in its comparison with similar therapeutic approaches. The above is the essence of a comparative study. However, such studies are not common. The article considers the problems associated with the use of indirect comparisons of new medical technologies in the absence of direct comparisons. General recommendations on conducting indirectcomparisons are provided. Possibilities of application of the results obtained in the course of indirect comparisons to conducting pharmacoeconomic analysis are shown.